Tuning the micromorphology and exposed facets of MnOx promotes methyl ethyl ketone low-temperature abatement: boosting oxygen activation and electron transmission. Issue 15 (10th July 2018) - Jian, Yanfei; Ma, Mudi; Chen, Changwei; Liu, Chao; Yu, Yanke; Hao, Zhengping; He, Chi
Abstract : MnO x nanowires with highly exposed {101} facets of Mn3 O4 possess excellent low-temperature activity and stability for methyl ethyl ketone destruction. Abstract : MnO x oxides with different morphologies (nanowire (MnO x -W), nanocube (MnO x -C), nanorod (MnO x -R), and nanosphere (MnO x -S)) and exposed facets were synthesized via a solvothermal method. The catalytic performance of the synthesized MnOx materials for methyl ethyl ketone (MEK) destruction was investigated. Results show that the activity of MnO x -W with highly exposed {101} facets of Mn3 O4 is superior to that of MnO x -C, MnO x -R, and MnO x -S exposing {321} facets of Mn2 O3, {110} facets of MnO2, and {101} and {112} facets of Mn3 O4, respectively. MEK can be completely mineralized into CO2 at 195 °C over MnO x -W under a relatively high gas hourly space velocity of 37 200 h −1, which is even better than some typical noble metal loaded catalysts. The lowest apparent activation energy of MnO x -W (27.7 kJ mol −1 ) for MEK destruction also confirms its excellent catalytic activity. Density functional theory (DFT) results reveal that the {101} facets of Mn3 O4 have the highest MEK adsorption energy (0.79 eV), which indicates that MEK molecules have a high affinity to adsorb onto the MnO x -W surface, promoting the oxidation process of MEK. In situ DRIFTS and TPSR results indicate that the mineralization of MEK into CO2 over MnO x -W goes through an oxidation route with diacetyl as the primary intermediate. We found that the highly exposed {101} active facets, abundant oxygen vacancies, and excellent low-temperature reducibility are responsible for the superior oxidation performance of MnO x -W. This finding may bring new insights into the designing of highly effective catalysts and has implications for a wide range of reactions not limited to MEK oxidation.